AngioJet Rheolytic Thrombectomy to Treat Inferior Vena Cava Filter-Related Thrombosis: Efficacy and Safety Compared With Large-Lumen Catheter Suction - Liu, Zhengli; Fu, Guanqi; Gong, Maofeng; Zhao, Boxiang; Gu, Jianping; Wang, Tao; Zhou, Yangyi; He, Xu; Kong, Jie (Frontiers in Cardiovascular Medicine, 2022)
Objective: To compare the efficacy and safety of AngioJet rheolytic thrombectomy (ART) and large-lumen catheter suction (LCS) in the treatment of inferior vena cava (IVC) filter related IVC-iliac vein thrombosis. Methods: The clinical data and medical imaging materials of 65 cases were collected, which suffered acute inferior vena cava filter related IVC-iliac vein thrombosis and received percutaneous mechanic thrombectomy (PMT) from June 2016 to June 2020 in our center, including 32 cases of LCS group and 33 cases of ART group. The final thrombolysis rate, the incidence of complications, and the follow-up are evaluated. Results: The limb swelling was significantly relieved in patients with PMT after treatment. The peri-diameter difference of the limb in the LCS group before and after treatment was [(5.20±2.03)cm vs. (2.17±1.29)cm, P< 0.05], and that in the ART group before and after treatment was [(4.79±2.23)cm vs. (1.74±0.94)cm, P < 0.05]. The amount of postoperative recombinant tissue-type plasminogen activator (rt-PA) is reduced in ART group [(57.97±21.25)mg in LCS group vs. (40.45±20.89)mg in ART group, P < 0.05], and the thrombolysis rate was higher than that of the LCS group [(74.13%±19.74% in LCS group ) vs. (84.58%±11.90% in ART group %), P < 0.05].No serious complications occurred during the treatment. Conclusion: Both LCS group and ART group have good thrombosis clearance effects on the inferior vena cava filter related IVC-iliac vein thrombosis. ART can reduce the rt-PA dose, increase the thrombolysis rate and reduce the risk of bleeding during thrombolysis.